2015
DOI: 10.1108/ijwis-08-2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

Measuring climate change on Twitter using Google’s algorithm: perception and events

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Studies have suggested that the public shows a preference for scientific publications with general keywords compared with those with complicated scientific jargon [47], lacking a deep understanding of the complicated issue [46] and the necessity for mitigation of the climate issue [47]. These conclusions seem to suit global warming more than climate change according to the current study, which is probably because climate change receives more publicity and recognition than global warming in the scientific community.…”
Section: Phenomenon Vs Mechanism Of Actionmentioning
confidence: 60%
See 1 more Smart Citation
“…Studies have suggested that the public shows a preference for scientific publications with general keywords compared with those with complicated scientific jargon [47], lacking a deep understanding of the complicated issue [46] and the necessity for mitigation of the climate issue [47]. These conclusions seem to suit global warming more than climate change according to the current study, which is probably because climate change receives more publicity and recognition than global warming in the scientific community.…”
Section: Phenomenon Vs Mechanism Of Actionmentioning
confidence: 60%
“…Therefore, semantic network analysis, a methodology based on cognitive science, could help researchers infer the hidden cognitive network structure in the human mind [44] based on the analysis of texts, as the frequency, semantic distance, and co-occurrence pattern of words can accurately reflect their meaning and links [45]. Several researchers have attempted to build a semantic network of certain climate events in social media discourse and scientific publications [46][47][48]. Research about public perceptions of global climate change in Qatar confirmed that the observed semantic network of climate concepts is not random and represents as meaningful clusters [49].…”
Section: Network Model For Cognitionmentioning
confidence: 99%
“…The hashtag "#climatechange" was selected because research has shown that awareness of climate change on Twitter is chiefly expressed using this hashtag (Hamed, et al 2015).…”
Section: Hashtagsmentioning
confidence: 99%
“…Bigrams, as network construction means, are widely used in various computational problems 48 . We present an incremental network construction approach that is wellknown in the literature in prominent algorithms (e.g., Prim's algorithm 49,50 ) which starts with an empty set of nodes and incrementally adds new nodes, one node at a time.…”
Section: Tfidf Feature Selection and Model Constructionmentioning
confidence: 99%